The prevalence of polypharmacy and hyper-polypharmacy among middle-aged vs. older patients in Saudi Arabia: a cross-sectional study - Alqurain, Aymen A.; Albaharnah, Murtada; Al Zayer, Samanah; Ameer, Luma; Ghosn, Sherihan; Al-Shaibi, Samaher; Algoraini, Marwa; Aldhafeeri, Amal; Alyusuf, Danah A.; Alshnbari, Afnan; Alsaffar, Nida; Al-Matouq, Jenan; et al. (Frontiers in Pharmacology, 2024)
Introduction. Polypharmacy, the use of multiple medications, is a growing concern among middleaged and older patients, posing potential risks and challenges in healthcare management.To identify the prevalence of polypharmacy and hyper-polypharmacy among populations of middle-aged vs older patients and identify its associated common comorbidities and prescribed medications in a large Qatif Central Hospital (QCH), Saudi Arabia.Methods. Patients aged 40 years or older, presented to an outpatient medical care clinic at QCH, Saudi Arabia between 1 st January and 31 st December 2021 were included and their comorbidities, prescribed medications and recent clinical laboratory test results were collected. Charlson Comorbidity Index (CCI) was calculated to predict the risk of mortality. Logistic regression was used to compute the association between the prevalence of polypharmacy and patient characteristics. The results were presented as odd ratios (OR) and 95% confidence intervals (95% CI).Results. A total of 14081 patients were included, 31% of the cohort were older patients and 66% of the cohort were identified with polypharmacy. The majority of the polymedicated patients were presented to an internal medicine care unit (34%). The prevalence of polypharmacy was positively associated with CCI (OR = 3.4, 95% CI 3.3 -3.6), having a disease related to the musculoskeletal system (MSD) (OR = 4.2, 95% CI 3.8 -4.7) and alimentary tract and metabolism (ATM) (OR = 3.8, 95% CI 3.4 -4.2). Conversely, the prevalence of polypharmacy was negatively associated with age (OR = 0.9, 95% CI 0.89 -0.91) and patients with cardiovascular diseases (OR = 0.6, 95% CI 0.5 -0.7).Polypharmacy is still an ongoing concern. Patients particularly, those with diseases related to MSD or ATM should be considered for pharmacists reviewing prescriptions to reduce the risk of adverse drug reactions and future consequences of polypharmacy.